Managerial ability and intellectual capital disclosure - Rajabalizadeh Javad; Oradi Javad (Emerald, 2022)
Purpose
While prior research in the area of intellectual capital (IC) disclosure has mainly focused on firm, board and audit committee characteristics, there is little research on whether managerial characteristics are associated with IC disclosure. This study aims to examine the relationship between managerial ability (MA) and the extent of IC disclosure.
Design/methodology/approach
The study sample comprises 1,098 firm-year observations of Iranian listed firms during 2012–2017. This study uses the checklist developed by Li et al. (2008) and adopts a content analysis approach and calculates the IC disclosure index in 62 dimensions within three categories: human capital, structural capital and relational capital. To measure MA, this study uses the managerial ability score (MA-Score) developed by Demerjian et al. (2012) for Iranian firms.
Findings
The results show that MA is significantly and negatively associated with the overall extent of IC disclosure and all the three components of IC (human capital, structural capital and relational capital). Further analysis shows that the interaction between MA and firm performance is positive and significant, suggesting that the negative relationship between MA and IC disclosure is less pronounced for high-performing firms. This study addresses the potential endogeneity issue by using the propensity score matching approach. The findings are also robust to the alternative measure of MA.
Originality/value
This study contributes to both the MA literature and the IC disclosure literature. To the best of the authors' knowledge, this study is the first to provide empirical evidence on the relationship between MA and IC disclosure.